Building Institutional Brand Personality: The Effect of the Creative Problem Solving Ability Attributes of School Managers - Semarco, Stanley K. M.; Cho, Seokhee (Journal of Communications, Media & Society, 2017)
The study examined the linkages between creative problem-solving ability attributes and the specific components of the institutional (corporate) brand personality dimensions; as well as the predictive influence of creative problem solving ability attributes on the aggregated institutional brand personality of Ghanaian basic schools. Two hundred and seventy-nine headteachers and 558 teachers provided data using the creative problem-solving ability attributes and brand personality dimensions inventories. The structural equation modelling result showed that the hypothesised model of the linkage between creative problem-solving ability attributes and institutional brand personality fit the data. Results also indicated that divergent thinking had a significant indirect effect on brand personality, with motivation and knowledge showing significant direct effects. The implication of the findings when it comes to school leaders creatively providing solutions and determining the schools brand personality was discussed.
Research Article
Keywords: Institutional Brand Personality, Creative Problem Solving, Ghana, School Managers